2020
DOI: 10.1002/pld3.297
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling reveals local and systemic responses of kiwifruit to Pseudomonas syringae pv. actinidiae

Abstract: Pseudomonas syringae pv. actinidiae (Psa), a bacterial pathogen, causes bacterial canker disease in kiwifruit. To elucidate the local and systemic influences of Psa infection on kiwifruit, comprehensive analyses were conducted by combining metabolomic and physiological approach under Psa‐infected treatment and mock‐inoculated control in leaves, stems, and bleeding saps. Our results show that Psa infection stimulated kiwifruit metabolic reprogramming. Levels of many sugars, fumarate, and malic acid were decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 56 publications
(82 reference statements)
0
25
0
Order By: Relevance
“…garcae. The decrease in sugars was observed by Li et al [15] in kiwi leaves infected with Pseudomonas syringae pv. actinidae (Psa).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…garcae. The decrease in sugars was observed by Li et al [15] in kiwi leaves infected with Pseudomonas syringae pv. actinidae (Psa).…”
Section: Discussionmentioning
confidence: 57%
“…Then, our results suggested that P. syringae pv. garcae may induce reduction in the compounds (sugars, phenolic compounds and flavonoids) in coffee seedlings during the infection process as observed in other pathosystems [ 15 , 34 ]. Higher concentrations of gallic, caffeic, and chlorogenic acids and the presence of vanillin were detected in the Iapar-59 cultivar inoculated with P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data showed that suppression of cell wall synthesis is crucial for Psa infection. However, our previous study showed that most of the phenolic compounds were reduced in ‘Jinkui’ but increased in ‘Hongyang’ after Psa inoculation, while lignin changed in the opposite direction ( Li et al, 2020 ), indicating that phenolic compounds were negatively related to kiwifruit Psa resistance, and lignin was positively related to kiwifruit Psa resistance. It has been reported that various MYB transcription factor genes, including a large class of plant transcription factors, directly or indirectly regulate the expression of lignin biosynthesis genes in many plant species ( Kim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…chinensis, including 'Hongyang, ' 'Hort16A, ' and 'Jintao' , are considered more susceptible to biovar 3 than A. chinensis var. deliciosa, including 'Jinkui' and 'Xuxiang' (Li et al, 2020;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%